Age of readiness for epilepsy surgery - Odinstova, Galina; Dengina, Nina (Nepal Journal of Neuroscience, 2022)
Introduction The average time between epilepsy onset and epilepsy surgery is currently approximately 20 years. In epilepsy, research on the problem of late referral for neurosurgical treatment is crucial. We aimed to investigate gender differences in the willingness of patients to undergo epilepsy surgery for focal drug-resistant epilepsy (DRE). Methods. It was a single-centre retrospective, observational, longitudinal cohort study in the outpatient and functional neurosurgery departments. We developed a structured questionnaire to examine patients’ demographic data, disease history, and perceptions of neurosurgical treatment (duration of epilepsy and optimal age for neurosurgery) in two gender groups. We examined data from 53 patients; eight people were dropped out from the research. Results. Ninety-four point three per cent of outpatients and inpatients answered in the affirmative form the question about their willingness to undergo epilepsy surgery for focal DRE. There were 26 men in group one and 19 women in group two. The disease had been present for 19.26 ± 1.35 years before epilepsy surgery or the decision to undergo surgery. Patients with no significant gender differences between groups considered that the ideal age for neurosurgery was 18.66 ± 1.3 years and that the optimal duration of the disease was 6.94 ± 1.02 years, which was two point eight times shorter than the actual duration of epilepsy. Conclusions. No gender differences in willingness to undergo surgical management of focal DRE were found. The subjective time in which a patient decides to undergo epilepsy surgery is much shorter than the objective time from epilepsy onset to neurosurgery. This could be one of the solutions to the problem of late referral for epilepsy surgery.